Aspectos produtivos e dinâmica parasitária em ovinos infectados naturalmente com Eimeria spp. Alimentados com dietas contendo níveis crescentes de borra de babaçu - REIS, Sara Silva (2022)
The objective was to evaluate the productive aspects and parasite dynamics in sheep naturally infected with Eimeria spp. fed diets containing levels of greasy babassu by-product. Twenty-eight male lambs were used, with an initial weight of 20±4kg and an average age of 5 months. The treatments consisted of four experimental diets with increasing levels of babassu sludge (0%, 5%, 10% and 15%) based on dry matter. A completely randomized design was used, with four treatments and seven replications. The dynamics of infection by Eimeria spp. was performed by means of coproparasitological exams in each sample according to the level of inclusion of babassu sludge on days (-7, 0, 14, 28, 42 and 49). In this study, nine species of Eimeria were identified, with a total prevalence of 93.45% of the fecal samples. The species E. crandallis, E. ovinoidalis, E. parva, E. bakuensis and E. faurei were more recurrent and their elimination peaks occurred on experimental day 28 at all levels of inclusion of greasy babassu by-product in the sheep diet. The inclusion of 9.05% of greasy babassu by-product in the sheep diet significantly reduced the oocyst count per gram of feces (P<0.05) without affecting the average daily gain (ADG) (P>0.05) and dry matter intake (DMI) (P>0.005). The first two principal components explain 54.54% of the total variation of the variables evaluated. The first component was related to the oocyst count per gram of feces and to Eimeria species and the second component to the nutrient consumption variables. It was observed that ADG (g/day) was negatively correlated with E. bakuensis and DMI (g/day) was negatively correlated with the mean of OOPG, E. bakuensis, E. ovinoidalis and E. faurei. Infection by Eimeria spp. negatively affects the DMI and weight gain of sheep. It is recommended the inclusion of 9.05% in the diet of sheep finished in confinement.